Melanopsin: From a small molecule to brain functions. (June 2020) - Duda, Mariusz; Domagalik, Aleksandra; Orlowska-Feuer, Patrycja; Krzysztynska-Kuleta, Olga; Beldzik, Ewa; Smyk, Magdalena Kinga; Stachurska, Anna; Oginska, Halszka; Jeczmien-Lazur, Jagoda Stanislawa; Fafrowicz, Magdalena; Marek, Tadeusz; Lewandowski, Marian Henryk; et al.
Highlights: Melanopsin plays a key role in biological responses of intrinsically photosensitive retinal ganglion cells. It triggers signal phototransduction responsible for several non-image forming functions. It is involved in pupillary light reflex, circadian rhythms, vision as well as cognitive and affective functioning. Abstract: Melanopsin, a G family coupled receptor, found within the ganglion cell layer in the retina, plays an important role in non-image-forming visual functions, including hormone secretion, entrainment of circadian rhythms, cognitive and affective processes. Diffuse projections of melanopsin-containing cells to many brain areas suggest that different responses may involve different neural projections, thus different melanopsin cells. Considering the complexity of the melanopsin system, its contribution to so many different biological functions is not surprising. In this review, we summarize the current knowledge about melanopsin in terms of its photophysics, photochemistry, mechanisms of activation, cell signaling, morphology, and physiology. In the last part, the role of melanopsin in image and non-image forming processes and cognitive and affective functioning of animals and humans, are discussed. Although in recent years considerable insight has been gained into the melanopsin system, it still remains an open question of how one protein expressed by several thousand cells in the retina, could be responsible for so many diverse functions and what activation mechanism(s) it uses.